Chemistry Laboratory Equipment as Authentic Materials in Assisting Tenth Graders of Vocational School in Writing Procedure Text - Imelda Mutiara Kansa; Esti Kurniasih (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study explores the use of chemistry laboratory equipment as authentic materials to support tenth-grade vocational students in writing procedural texts. Conducted at a vocational school in Surabaya, 36 students from the Chemical Engineering Department participated in learning activities, observations, interviews, and writing tasks. Results showed that integrating real tools enhanced students’ understanding of text structure, vocabulary, and sequencing. Most students produced well-organized texts and expressed higher motivation and confidence. Despite some challenges in transferring practical experience into written form, the findings affirm the value of authentic materials in genre-based ESP writing instruction for vocational contexts.